Increased Hydrostatic Pressure Promotes Primary M1 Reaction and Secondary M2 Polarization in Macrophages - Wang, Bo; Kasper, Maren; Laffer, Björn; Meyer zu Hörste, Gerd; Wasmuth, Susanne; Busch, Martin; Jalilvand, Tida Viola; Thanos, Solon; Heiligenhaus, Arnd; Bauer, Dirk; Heinz, Carsten (Frontiers in Immunology, 2020)
Patients with chronic anterior uveitis are at particularly high risk of developing secondary glaucoma when corticosteroids (e.g., dexamethasone (Dex)) are used or when inflammatory activity has regressed. Macrophage migration into the eye increases when secondary glaucoma develops. By using a pressure chamber cell culture system, we assessed the effect of increased hydrostatic pressure (HP), inflammation, and immunosuppression (Dex) on the M1/M2 phenotype of macrophages. Bone marrow-derived macrophages (BMDMs) were stimulated with medium, lipopolysaccharide (LPS, 100 ng/ml), Dex (200 ng/ml), or LPS+Dex and incubated with different HP (0, 20 or 60 mmHg) for 2 or 7 days. The numbers of CD86+/CD206- (M1 phenotype), CD86-/CD206+ (M2 phenotype), CD86+/CD206+ (intermediate phenotype), F4/80+/TNF-α+, and F4/80+/IL-10+ macrophages were determined by flow cytometry. TNF-α and IL-10 levels in cell culture supernatants were quantified by ELISA. TNF-α, IL-10, fibronectin, and collagen IV expression in BMDMs were detected by immunofluorescence microscopy. Higher HP polarizes macrophages primarily to an M1 phenotype with less extra cellular matrix (ECM) production and secondary to an M2 phenotype with enhanced ECM production. Dex induces an M2 phenotype with more ECM production. Higher HP further increased M2 polarization of Dex-treated macrophages. These changes in the M1/M2 phenotype by high HP or Dex treatment may play a role in the pathogenesis of secondary uveitic glaucoma- or glucocorticoid (GC)-induced glaucoma.